1998
DOI: 10.1094/pdis.1998.82.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Ophiostoma quercus and Ceratocystis fagacearum by Nitidulids from O. quercus-Colonized Oak Wilt Mats

Abstract: Field experiments were conducted to determine whether the frequency of Ceratocystis fagacearum and Ophiostoma quercus propagule acquisition by nitidulids visiting oak wilt fungal mats is affected by the presence of O. quercus on the mats. Augmentation sprays with O. quercus were used to achieve different levels of mat colonization by that fungus. The extent of colonization by O. quercus 7 to 14 days after spraying was greatest for postmature mats with open cracks (>0.5 cm) observed on the spray date (P< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Species of Ceratocystis, particularly those in the C. fimbriata s.l. species complex, are known to have close associations, mainly with casual insects ( Jewell 1956, Juzwik and French 1983, Juzwik et al 1998. Ceratocystis fimbriata s.l.…”
Section: Discussionmentioning
confidence: 99%
“…Species of Ceratocystis, particularly those in the C. fimbriata s.l. species complex, are known to have close associations, mainly with casual insects ( Jewell 1956, Juzwik and French 1983, Juzwik et al 1998. Ceratocystis fimbriata s.l.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal propagules are transmitted to the wounds mainly through sap‐feeding beetles (Coleoptera: Nitidulidae) (Kamgan Nkuekam et al , ), wind (Wingfield et al , ) or silvicultural practices (Uzunovič et al , ). Sap‐feeding beetles have been shown to move O. quercus in the USA into wounds (Juzwik & French, ; Juzwik et al , ). Kamgan Nkuekam et al () have demonstrated that the nitidulid beetles Brachypeplus depressus and Carpophilus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the Microascales, species in various genera of the Ceratocystidaceae are serious pathogens (Roux and Wingfield 2009;. For example, Ceratocystis albifundus is an important pathogen of Acacia mearnsii in South Africa (Roux et al 1999), C. manginecans causes a serious disease of mango and Acacia mangium trees (Van Wyk et al 2007;Tarigan et al 2011) and Ceratocystis fagacearum causes oak wilt in North America (Henry et al 1944, Juzwik et al 1998). Other members of the ophiostomatoid fungi are, however, considered to be saprophytes or agents of sap stain Thwaites et al 2005;Harrington et al 2010).…”
Section: Introductionmentioning
confidence: 99%